Evaluation of the MEC's poverty-alleviation programme in the Waterberg District of the Limpopo Province - Letshokgohla, Motlatso Elias (My University, 2009)
Background: In 2003, the Limpopo Department of Health and Social Development introduced a system to train students from poor families as auxiliary nurses as a poverty-alleviation strategy in the province. The programme was aimed at targeting the needy: those who depended on social grants for a living, were orphaned or who headed a family. Five years have passed but no formal evaluation has been done to estimate the impact of the programme. Objective: To evaluate the self-reported impact of auxiliary nursing training of youth from poor families in the Waterberg District on alleviation of their poverty Methodology: A cross-sectional study design using an anonymous structured questionnaire. The study population included 200 auxiliary nurses trained through the programme from 2003 to date. Results: This research found conclusive evidence that the poverty alleviation project in the Limpopo Province has significantly improved the economic conditions of the beneficiaries such as number of rooms in their houses, type of houses, type of floors, refuse collection, indoor water supply, indoor flash toilet, household assets, access to water and wood, number of meals, transport and domestic workers. This study also found positive changes in family income, bank and other accounts. This study shows significant changes in asset indicator scores after respondents had joined the programme. Conclusion: This is the first study to systematically evaluate a poverty alleviation programme in South Africa. Hopefully, both the Department of Finance and the Department of Health and Social Development in the Limpopo Province would utilise the findings of this study to review and to improve other poverty alleviation programmes in the Waterberg District and the Province.
Keywords: poverty-alleviation; Limpopo Province